Kandungan Nitrogen dan Bobot Biji Kentang yang Diberi Pupuk Organik Difermentasi, Azospirillum Sp., dan Pupuk Nitrogen di Cisarua, Lembang, Jawa Barat - . Nurmayulis; . Maryati (JOURNAL OF TROPICAL SOILS, 2008)
A research was conducted to study response of potato (Solanum tuberosum L.) plant to the application of  fermented organic matter (‘porasi’) (0, 7.5, 15.0, and 22.5 t ha-1), without or with inoculation of Azospirillum sp., and N fertilizer (0, 86, 172, and 258 kg ha-1 N) and also to determine optimal rate of application of ‘porasi’ and N fertilizer without or with inoculant Azospirillum sp.  Field experiments were carried out in Cisarua, Lembang West Java, from June 2003 to Nov. 2003.  The experiments were done in a Randomized Block Design of factorial pattern of three factors, were replicated three times.  Results of the experiments showed that: (1) N contents were higher as rates of ‘porasi’ and N fertilizer increased and with inoculation of Azospirillum sp.,  whereas the highest N concentration was obtained due to application of 22.5 t ha-1 ‘porasi’ with inoculation of  Azospirillum sp. and application of N fertilizer of 258 kg ha-1, and (2) the optimum rate of  ‘porasi’ and N fertilizer without inoculation of Azospirillum sp. was 15.287 t ha-1 and 228.519 kg ha-1 N, respectively, to obtain maximum yield of 6.028 kg per plot or 25.117 t ha-1, whereas with inoculation of  Azospirillum sp. the optimum rate of ‘porasi’ and N fertilizer was 16.464 t ha-1 and 190.110 kg ha-1 N,  respectively, with maximum yield of 6.493  kg per plot or 27.054  t ha-1.